Routine Work Instability and Workplace Incivility: The Moderated Mediation Model of Employee Frustration and Family Motivation - Bilal, Ahmed; Tufail, Sajid; Mukhtar, Sana; Kharal, Mina (Pakistan Journal of Humanities and Social Sciences, 2024)
This research examines the effect of routine work instability on workplace incivility. It also investigates the mediating role of frustration and moderating role of family motivation in this relationship. The data collected from 221 employees and their immediate supervisors, was analyzed using structural equation modeling. The results revealed that routine work instability has a significant effect on workplace incivility via employee frustration. The results further showed that family motivation positively moderates the impact of routine work instability and employee frustration. This study can help managers control employee frustration and bad behavior due to the sudden changes in the timetable. Additionally, it can help organizations understand the consequences and effects of schedule changes in the timetable of the workers.